Setting-up a 3D Integrated Petrophysical Model Using Petrel software for Mishrif Formation in Garraf Oil Field, Southern Iraq - Al-Yasi , Ameen I.; A. Jaed, Mustafa; Hasan, Firas N. (Iraqi Journal of Science, 2022)
Setting-up a 3D geological model both from field and subsurface data is a typical task in geological studies involving natural resource evaluation and hazard assessment. In this study a 3D geological model for Mishrif Formation in Garraf oil field has been set-up using Petrel software. Mishrif Formation represents the most important reservoir in Garraf oil field. Four vertical oil wells (GA-4, GA-A1P, GA-3 and GA-5) and one directional well (GA-B8P) were selected in Garraf Oil Field in order to set-up structural and petrophysical (porosity and water saturation) models represented by a 3D static geological model in three dimensions. Structural model shows that Garraf oil field represents a domal structure that shows continuous growth as indicated by the structural maps at top of reservoir units. The structural closure is shifted from GA-3 well to GA-A1P well. Mishrif Formation was divided into ten zones (top Mishrif, M1, M1.2, M2, L1, L1.2, L2, L2.2, L2.3 and L2.4.). Petrophysical model (porosity and water saturation) for Mishrif Formation was set-up from values of porosity and water saturation using Sequential Gaussian Simulation algorithm. According to data analyses and the results from modeling the units (M1.2, L1 and L1.2) are considered as high quality reservoir units due to the high PHIE and low water saturation. Units (L2, L2.2, L2.3 and L2.4) are considered as poor reservoirs because of low PHIE and high water saturation, and non-reservoir units include (Top Mishrif, M1 and M2) therefore, they represent cap units. Cross sections of petrophysical model were conducted to illustrate the vertical and horizontal distribution of porosity and water saturation between wells in the field.